Long-term effects of gastric bypass surgery on psychosocial well-being and eating behavior: not all that glitters is gold. Issue 6 (1st November 2016) - Vangoitsenhoven, Roman; Frederiks, Pascal; Gijbels, Brecht; Lannoo, Matthias; Van der Borght, Wout; Van den Eynde, Amber; Mertens, Ann; Mathieu, Chantal; Van der Schueren, Bart
Abstract : Objectives: The aim of this pilot study was to evaluate long-term effects of Roux-en-Y gastric bypass (RYGB) on physical and psychosocial health as well as eating behavior of obese patients. Methods: We compared 23 patients 7 years after RYGB to 23 body mass index (BMI), sex, and age matched obese control patients by means of self-reporting questionnaires: Hospital Anxiety and Depression Scale (HADS), Quality of Life Enjoyment and Satisfaction Questionnaire – Short Form (Q-LES-Q SF), Dutch Eating Behavior Questionnaire (DEBQ), and Alcohol Use Disorders Identification Test (AUDIT). Data are presented as median ± interquartile rage. Results: Physical health had improved and body image (80 ± 25% vs. 20 ± 49%, p  < 0.001) was better in post-RYGB patients when compared to controls. HADS-depression score (4 ± 8 vs. 11 ± 9; p  = 0.005) was lower post-RYGB. Satisfaction with physical health (2 ± 2 vs. 2 ± 1, p  = 0.037), daily life functioning (4 ± 2 vs. 2 ± 2, p  = 0.050), and hobbies (4 ± 1 vs. 2 ± 2, p  = 0.011) was higher post-RYGB, but social relationships and sexual performance were not perceived as superior. In addition, post-RYGB patients were more prone to eat on external cues (13 ± 7 vs. 19 ± 13; p  = 0.007). Conclusion: Seven years post-RYGB, patients reported a significant improvement of physical health and higher satisfaction with daily life, but not with social relationships or sexual performance. Eating behavior post-RYGB was more influenced by external cues.